The Effectiveness on the use of Zoom Application in Learning Discourse Analysis at 6th Semester of English Education Department Universitas Muhammadiyah Sidenreng Rapp - Sam Hermansyah; Buhari .; Andi Asrifan; Nadirah .; Yuliana mansyur; Firman Saleh; Fatimah . (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
This study aims to determine the effectiveness of using the Zoom application in learning Discourse Analysis during the Covid-19 pandemic in the sixth semester of the English Education Department at Muhammadiyah University of Sidenreng Rappang. The data was collected through questionnaires and interviews. This research includes qualitative research with descriptive qualitative. The subject of this research are 30 students. Sampling in this study using purposive sampling, where's the sampling technique is to take 15 students. The results showed that the effectiveness on the use of zoom application in learning discourse analysis during the covid-19 pandemic carried out by students was less effective. Because of the many obstacles experienced during the learning process, such as being constrained by the lack of a network that makes it difficult for students to understand the material presented by the lecturer. As conclusion, zoom application is less able to help in learning, especially online discourse analysis learning.